Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1161/01.res.84.11.1252
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in Neointimal Hyperplasia in the Rat

Abstract: Abstract-We performed an initial screen of 11 rat strains by use of a standard balloon injury to the left iliac artery to observe whether genetically determined differences existed in the development of neointimal hyperplasia. Neointimal hyperplasia was assayed 8 weeks after the vascular injury on coded microscopic sections. Statistically significant differences in the percentages of the vascular wall cross-sectional areas composed of intima (percentage intima) secondary to neointimal hyperplasia were noted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
2
29
1
2
Order By: Relevance
“…Inbred SHR and BN rats were obtained from Harlan Sprague-Dawley (Indianapolis, IN) and were maintained in the Division of Laboratory Animal Medicine at the Medical University of Ohio, where the genetic crosses were bred. Our previous experiments suggested that the alleles responsible for NIH growth were inherited in a codominant manner (1), and thus we selected an F 2 (SHR ϫ BN) intercross population for the genome scan. Female SHR and male BN rats were intercrossed to produce F 1 (SHR ϫ BN) progeny that were then used to breed an F 2 (SHR ϫ BN) population of 301 males.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Inbred SHR and BN rats were obtained from Harlan Sprague-Dawley (Indianapolis, IN) and were maintained in the Division of Laboratory Animal Medicine at the Medical University of Ohio, where the genetic crosses were bred. Our previous experiments suggested that the alleles responsible for NIH growth were inherited in a codominant manner (1), and thus we selected an F 2 (SHR ϫ BN) intercross population for the genome scan. Female SHR and male BN rats were intercrossed to produce F 1 (SHR ϫ BN) progeny that were then used to breed an F 2 (SHR ϫ BN) population of 301 males.…”
Section: Methodsmentioning
confidence: 99%
“…Drug-eluting stents reduce the occurrence of short-term NIH to 20 -30%, but the long-term efficacy of these devices is not known (27). NIH is also associated with the development of significant restenosis in 20% of patients undergoing carotid endarterectomy (1) and is a major contributor to graft failure in coronary and peripheral arteries (24).…”
mentioning
confidence: 99%
See 3 more Smart Citations